Fractional dose verification of intensity-modulated radiotherapy for cervical cancer based on exit fluences and Log files. Issue 1 (March 2023) - Tan, Xia; Li, Qicheng; Luo, Huanli; Li, Shi; Li, Mengze; Jin, Fu
Abstract: To investigate the feasibility of fractional dose verification (DV) using the exit fluence (Flux) and log file (Log) of intensity-modulated radiotherapy (IMRT) for cervical cancer. Fluxes and Logs were collected from an Alderson radiotherapy (ART) phantom and 17 cervical cancer patients, respectively. Fluxes were measured with an electronic portal imaging device for 2D-DV using γ index and dose difference (DD). Logs were retrieved from the Aria server and used to reconstruct the 3D dose by combining the planned CT data for 3D-DV using γ index. The ART position was changed from 0.1 cm to 1 cm with a step size of 0.2 cm and from 1 cm to 3 cm with a step size of 1 cm to test the accuracy of 2D-DV. The correlations between the phantom's DV results and its positioning errors (PEs) were analyzed, as were those between the patients' DV results and their treatment fractions (TFs). For 2D-DV, the γ value of each field with 3%/3 mm criteria in the ART phantom was more than 95% when a PE was ≤5 mm. The same PE introduced using DD3% caused the passed rates to fall below the 95% tolerance. Both γ and DD showed negative correlations with PEs (R ∈ [–0.997, −0.765], P < 0.05). In 82.35% of patients, gamma values with 3%/3 mm criteria exceeded 86% in all TFs, and were greater than 93% in 98.38% of TFs. For the other patients, the γ values ranged from 38 to 100% due to significant reductions of their bladder volume and target. It displayed negative correlations with the TFs ( R ∈ [–0.903, −0.824], P  < 0.05). For 3D-DV, no significant relationship was found between the γ values with 1%/1 mm criteria and the ART PEs or the TFs of all patients ( P  < 0.05). The daily DV method using the Flux and Log could be used to detect the positioning errors, as well as anatomical changes.